Principles of Orthoplastic Surgery for Lower Extremity Reconstruction: Why Is This Important? - Azoury, Saïd C.; Stranix, John T.; Kovach, Stephen J.; Levin, L. Scott (Journal of Reconstructive Microsurgery, 2019)
Background Regardless of the antecedent etiology, lower extremity salvage and reconstruction attempts to avoid amputation, restore limb function, and improve quality of life outcomes. This goal requires a treatment team well versed in neurovascular pathology, skeletal and soft tissue reconstruction, and physical rehabilitation.Methods A review was performed of historical milestones that lead to the development of orthoplastic extremity reconstruction, principles of current management and the evidence that supports an orthoplastic approach. Based on available evidence and expert opinion, the authors further sought to provide insight into the future of the field centered around the importance of a multidisciplinary management protocol.Results Historically, orthopaedic and plastic surgeons worked separately when faced with challenging reconstructive cases involving lower extremity skeletal and soft tissue reconstruction. With time, many embraced that their seemingly separate skill-sets and knowledge could be unified in a collaborative orthoplastic approach in order to offer patients the best possible chance for success. First coined by the senior author (LSL) in the early 1990s, the collaborative orthoplastic approach between orthopaedic and plastic surgeons in limb salvage for the past several decades has resulted in a unique field of reconstructive surgery. Benefits of the orthoplastic approach include decreased time to definitive skeletal stabilization/soft tissue coverage, length of hospital stay, post-operative complications, need for revision procedures and improved functional outcomes.Conclusion The orthoplastic approach to lower extremity reconstruction is a collaborative model of orthopaedic and plastic surgeons working together to expedite and optimize care of patients in need of lower extremity reconstruction. The implementation of protocols, systems, and centers that foster this approach leads to improve outcomes for these patients. We encourage centers to embrace the orthoplastic approach when considering limb salvage, as the decision to amputate is irreversible.
Keywords: lower extremity; reconstruction; orthoplastic; flap; free flap